Multiple cervical spondylolisthesis and thoracic vertebral malformation in an 11 month-old Chilean Caballo Raza Chilena colt - Dorner, Cristóbal; Encalada, Javiera; Maldonado, Jorge; Palmero, Joanie (Austral Journal of Veterinary Sciences, 2022)
Compressive myelopathy caused by developmental cervical and thoracic malformation was diagnosed in an 11-month- old Chilean Caballo Raza Chilena colt. The patient evidenced an abnormal wide-based stance, neck muscle atrophy, upside-down neck conformation and tetra ataxia. Ataxia was exacerbated when the colt was walked down and uphill, walked with elevated head, backing and turning in tight circles. The patient showed no improvement following medical therapy, therefore, the colt was euthanised due to a poor prognosis after myelogram findings. Cervical spine malalignment (spondylolisthesis) associated with multi-level compression of the spinal cord was suspected based on cervical radiographs and myelogram findings and was confirmed postmortem. Thoracic vertebral malformation retained cartilage matrix spicules and a flare of the cranial vertebral epiphysis of the first thoracic vertebrae (T1) were also diagnosed at necropsy.